MODERATED MEDIATION OF ENTREPRENEURSHIP EDUCATION, SATISFACTION WITH ENTREPRENEURSHIP EDUCATION AND ENTREPRENEURIAL INTENTIONS IN VOCATIONAL EDUCATION AND TRAINING (NAU Journal of Technology and Vocational Education, 2025)
Career, vocational, and higher education literature have relatively established that entrepreneurship education (EE) has direct link with entrepreneurial intentions (EIs) and has also considered the role of attitude in link, yet scholars rarely take into account the nomological network of the link with specific attention on the role of student satisfaction with EE. Supported with the theory of planned behaviour (TPB), this study explored the sequential roles of satisfaction with entrepreneurship education (SWEE) and personal attitude (PAT) in the link between EE and EI among higher education students (HES). The study further explored the moderating role of gender in the nomology. To cover HES with varieties of specialties who have been engaged in EE in more than one academic semester, the participants (N = 165) were drawn from technology and business education programmes in a university in Nigeria. By employing structural equation modelling, the findings of the study revealed direct association of EE with EIs, with no sequential indirect effects of SWEE and PAT. The result showed that PAT mediated the pathway from EE to EIs. However, gender moderated how EE influences EIs. Implications are therefore discussed.
Keywords: Entrepreneurship; entrepreneurial intention; entrepreneurial education; satisfaction with entrepreneurship education; vocational educational and training